Easy to Love Pina Bausch's Masurca Fogo reviewed - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Review of Pina Bausch's Tanztheater Wuppertal. PALABRAS CLAVE: Pina Bausch, Masurca Fogo, Tanztheater Wuppertal.
Keywords: Bausch, Pina -- 1940-2009